2010
DOI: 10.4103/0973-7847.70920
|View full text |Cite
|
Sign up to set email alerts
|

Salvadora persica

Abstract: Salvadora persica (kharijal) is a large, well-branched, and evergreen shrub or a tree resembling Salvadora oleoides (meethijal) found in the dry and arid regions of India. Chewing sticks have been used for centuries for tooth cleaning, and are recommended by the World Health Organization in areas where their use is customary. Salvadora persica has enormous reported activities. It has potential medicinal and research activities. Salvadora persica is a promising product and is useful to produce antiplaque, analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 13 publications
1
32
0
2
Order By: Relevance
“…S. persica L. roots/stems known with various names like Mustard tree, Miswak, Koyojii and Pilu have been traditionally used for maintaining oral hygiene for centuries [3,4,6]. In this study, essential oils of dried (MD-1) and fresh (MF-1) roots of S. persica L. were isolated and the main components from the both oils were identified as benzyl isothiocyanate (MD-1; 68.1% and MF-1; 85.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. persica L. roots/stems known with various names like Mustard tree, Miswak, Koyojii and Pilu have been traditionally used for maintaining oral hygiene for centuries [3,4,6]. In this study, essential oils of dried (MD-1) and fresh (MF-1) roots of S. persica L. were isolated and the main components from the both oils were identified as benzyl isothiocyanate (MD-1; 68.1% and MF-1; 85.0%).…”
Section: Discussionmentioning
confidence: 99%
“…S. persica L., native to middle East and Africa, is a small well branched shrub with greenish yellow flowers and small red fruits when ripe. It grows up to a maximum height of 6-7 m with greenish small leaves (3.8-6.3 by 2-3.2 cm), having a robust aroma of cress or mustard [4,5]. S. persica L. roots/stems are known with various names like Mustard tree, Miswak, Koyojii and Pilu in Gulf region, Japan and India, respectively and have been traditionally used for maintaining oral hygiene for centuries [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Chewing sticks of S. persica have been used for centuries for tooth cleaning, and are recommended by the World Health Organization, in areas where their use is customary. A number of scientific studies have demonstrated that S. persica possesses anti-bacterial, anti-fungal, anti-viral, anti-cariogenic, anti-plaque, antiinflammatory, hypoglycemic, hypolipidemic, anti-osteoporosis, antioxidant, anti-ulcer, anti-convulsant, sedative and analgesic effects [7][8][9][10][11]. S. persica extracts exhibited antibacterial activities against 10 multidrugresistant bacterial clinical isolates other than oral pathogens in vitro [12].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of S. persica are eaten as a vegetable in the eastern tropical Africa and are used in the preparation of a sauce, tender shoots and are eaten as salad [3]. Recent investigations showed that S. persica has hypoglycemic and hypolipidemic activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%